2015
DOI: 10.1038/jp.2015.8
|View full text |Cite
|
Sign up to set email alerts
|

Mask ventilation with two different face masks in the delivery room for preterm infants: a randomized controlled trial

Abstract: The use of either face mask during PPV in the delivery room yields similar mask leak in preterm infants <33 weeks gestational age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…During PPV and SI, the default settings were gas flow of 8 L/min, PIP of 24 cmH 2 O and PEEP of 6 cmH 2 O. Staff members attending deliveries were trained to use the device and were familiar with both face masks 23. During PPV, respiratory rate was aimed at 40–60/min.…”
Section: Methodsmentioning
confidence: 99%
“…During PPV and SI, the default settings were gas flow of 8 L/min, PIP of 24 cmH 2 O and PEEP of 6 cmH 2 O. Staff members attending deliveries were trained to use the device and were familiar with both face masks 23. During PPV, respiratory rate was aimed at 40–60/min.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to other masks previously tested in manikin models8 9 or infants4 this is the first mask showing a reduction in leak compared with the conventional mask. This might be due to the sealing effect of the negative pressure between the inner and outer rims of the suction mask.…”
Section: Discussionmentioning
confidence: 80%
“…However, delivering effective mask ventilation can be challenging, because of large leak around the mask. Studies report variable leak, sometimes >50% of inspiratory volume, during mask PPV in preterm infants in the DR 3 4…”
Section: Introductionmentioning
confidence: 99%
“…Although the decision of face masks used could have introduced bias, the research team had no influence in this decision. Nonetheless, a recent study by Cheung et al, 19 compared Fisher and Paykel and Laerdal round face masks and reported no difference in mask leak between the 2 masks. Therefore, we believe this bias would be negligible in the current study.…”
Section: Discussionmentioning
confidence: 95%
“…11 This is further supported by ECO 2 measurements in 20 term infants over the first 120 seconds after birth. 13 Overall, it took a median (range) of 3 (1-8) breaths or 15 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) seconds after birth until ECO 2 was first detected. Once ECO 2 was detected, it increased significantly, and this was also associated with increases in V T , suggesting facilitation of FRC and lung aeration.…”
Section: Discussionmentioning
confidence: 99%